Revisiting rights - Sarat, Austin (Studies in law, politics, and society, 2009)
Rights and rights talk have a long and storied history and have occupied a crucial place in the ideology of liberal legalism. With the development of Critical Legal Studies in the 1970s and 80s, rights were subject to extensive critique. Yet not long after that critique rights were rehabilitated by feminists and Critical Race Theorists. Today, scholars are investigating the role of rights in social movements, in legal consciousness, in organizations, in the international arena, etc. This volume of "Studies in Law, Politics, and Society" contains a Special Issue on rights. It brings together the work of leading scholars to think about the nature, utility and limits of rights. This work takes stock of the field, charts its progress and points the way for its future development.